Efek Pemberian Kelor (Moringa oleifera Lam.) pada Pakan terhadap Gambaran Hemoglobin Sapi Ongole - Detha, Annytha Ina Rohi; Marumata, Dikhi; Datta, Frans Umbu; Ndaong, Nemay; Foeh, Nancy (JURNAL KAJIAN VETERINER, 2021)
The Miracle Tree has been known as a plant that contains complete nutrition which has anti-anaemia properties. This study aims to study the effect of adding Moringa to feed on the image of blood haemoglobin in cattle, especially Sumba Ongole cattle. The study was conducted in 2017, at the Integrated Dryland Laboratory of the University of Nusa Cendana and the Health Laboratory of the East Nusa Tenggara Province Health Service. The sample in this study were 12 Sumba Ongole cattle aged 2-3 years with a bodyweight of 210.5 kg- 249 kg. Treatments on cattle were divided into 4 groups. The results of the study showed that the haemoglobin level on day 0 of each treatment was still within normal limits. On days 25 and 50, each treatment was in the normal range of haemoglobin levels. Based on the results of the study, it was concluded that statistically giving Moringa flour to the feed had a significant effect on the haemoglobin levels of Ongole cattle.